Stand dynamics as a basis for ensuring the principle of sustainable forest management on the example of the stand of an atypical selection structure in the management unit “Tara” - Popović Aleksandar; Medarević Milan; Obradović Snežana; Pantić Damjan; Borota Dragan (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu)
The subject of the research is the selected stands in the Tara National Park, the Tara plateau mountain range within the management unit (MU) of the same name. These stands occupate over 90% of the total area of the MU and from a management aspect are characterized by structural neglect, significant deviation from the balanced state. The basic assumption of the research is reflected in testing the possibility of a significant impact on improving the structure of these forests during the management period and the possibility of recognizing the direction of their development as a result of the application of different treatments. Testing this assumption was carried out in relation to felling according to the real (planned allocation), possible (allocation in different stand situations in a specific section on six test surfaces of 10 ares each) and the assumed allocation (theoretical category). The development assessment was carried out according to the results of the impact of allocation (felling) on the change in the state at the end of the management period. To achieve the set goal, one section (section 66, section a) was selected as a typical representative of these stands. The results obtained indicate that the tested different variants of the referral can only partially correct the structural neglect of the stand. By applying the last (theoretical) variant of the referral, positive development elements of the stand are partially achieved (reducing the number of trees above the diameter of the cutting maturity). By analyzing the results, we conclude that recognizing the direction of stand development and its direction is the primary category of activity in a management period. The normal selection structure as a theoretical category is at the same time the main goal of its existence towards which it is necessary to direct activities. In specific stand forms, the main recommendation relates to understanding the problem as a long-term category, with elements that indicate an improvement in the condition at the end of the management period.